-4u+31=-9(u-9)

Simple and best practice solution for -4u+31=-9(u-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4u+31=-9(u-9) equation:


Simplifying
-4u + 31 = -9(u + -9)

Reorder the terms:
31 + -4u = -9(u + -9)

Reorder the terms:
31 + -4u = -9(-9 + u)
31 + -4u = (-9 * -9 + u * -9)
31 + -4u = (81 + -9u)

Solving
31 + -4u = 81 + -9u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '9u' to each side of the equation.
31 + -4u + 9u = 81 + -9u + 9u

Combine like terms: -4u + 9u = 5u
31 + 5u = 81 + -9u + 9u

Combine like terms: -9u + 9u = 0
31 + 5u = 81 + 0
31 + 5u = 81

Add '-31' to each side of the equation.
31 + -31 + 5u = 81 + -31

Combine like terms: 31 + -31 = 0
0 + 5u = 81 + -31
5u = 81 + -31

Combine like terms: 81 + -31 = 50
5u = 50

Divide each side by '5'.
u = 10

Simplifying
u = 10

See similar equations:

| x+5x=215 | | 3w-(7-w)=13 | | 2x-5y-27=0 | | -16a^2+49b^2=0 | | 4+-2+-1+6+2+-3+-3+-3= | | 5m+3m-2m=23 | | 4w^2+4w+3=0 | | -64x^2+81=0 | | (2b+5)-(b+2)= | | 8+y=-20 | | 8y+5-3=4y-22 | | 8+y=20 | | 6n+3(3n-8)-2= | | 12+12+x+x=p | | 36y^2-25z^2=0 | | A(3x-8)=18x | | -4g+7=13 | | 49-25m^2=0 | | Y*y+y=247 | | 7m-3m=6 | | 6y+5=11 | | -10a+22=-5(3+2a) | | 25=a+13-4s | | 36-12x=-6x-36 | | 2x-6(x-2)+x= | | 8k+6=46 | | 3-12x=-93 | | 3-12x=-93 | | (12b+6)+(3b-8)= | | 755=510+35n | | x^2-3x-8=-2x^2+8x-4 | | -2x+4=5-3z |

Equations solver categories